Pembatasan Kewenangan Presiden dalam Memberikan Dukungan Terhadap Bakal Calon Presiden dan atau Bakal Calon Wakil Presiden untuk Mewujudkan Pemilihan Umum yang Demokratis dan Berintegritas - Irwan, Muhamad; Saleh, Moh. (Legal Standing : Jurnal Ilmu Hukum, 2025)
This research examines the importance of limiting presidential authority in supporting presidential and/or vice presidential candidates in order to realize democratic elections with integrity. In the Indonesian political system, the president's position is very central, and his enormous influence has the potential to be abused if the president is directly involved in campaign support, which could distort the principle of equal opportunity for all candidates. Law Number 7 of 2017 concerning Elections and other regulations have emphasized the importance of the neutrality of state officials to ensure that elections run according to the principles of honesty and justice. The legal problem of presidential neutrality in holding elections is a crucial issue that needs to continue to be studied. This research uses normative legal methods, focusing on literature review and analysis of statutory regulations, including the 1945 Constitution and Law no. 7 of 2017 concerning Elections. Primary data includes statutory regulations, while secondary data comes from legal literature, previous research documents, and reports from election monitoring institutions. The analysis was carried out qualitatively with statutory interpretation, comparative analysis and theoretical analysis. The research results show that the legal basis for limiting presidential authority is clearly regulated in the 1945 Constitution (Article 6A paragraph (1) and Article 28D paragraph (1)) as well as Law no. 7 of 2017 (Article 282 and Article 283) Violations of the president's neutrality could have implications for ethical sanctions by the DKPP, lawsuits over election results at the Constitutional Court, legitimacy crises and political instability. This study confirms that the president's neutrality is in line with the principles of deliberative democracy and constitutionalism, where abuse of power can harm the principles of healthy democracy. strengthening the legal framework, monitoring mechanisms, and civil society participation to overcome weaknesses in the monitoring system and ensure democratic elections and integrity.